MOLECULAR MECHANISMS OF OPTIC NERVE DAMAGE: THE ROLE OF ANTHOCYANOZIDES IN THE PREVENTION OF RETINAL GANGLION CELL DEATH - V. V. Neroev; T. N. Kiseleva; Ì. S. Zaitsev (Российский офтальмологический журнал, 2018)
The literary review focuses on the dysfunction of endoplasmic reticulum (EPR), the role of EPR stress and oxidative stress in the pathogenesis of optic nerve damage. The data on the molecular mechanisms of optic nerve damage are given: these include the expression of genes and molecular chaperones, which are related to EPR stress and antioxidant protection. The studies into oral administration of bilberry extract anthocyanosides showed elevated levels of molecular chaperones in retinal ganglion cells (RGC). The chaperones suppress EPR stress and produce a positive effect on the metabolic activity of the cells. Thus, bilberry extract anthocyanosides may be considered as neuroprotectors in combined treatment of retinal pathology and glaucoma. For citation: Neroev V.V., Kiseleva T.N., Zaitsev М.S. Molecular mechanisms of optic nerve damage: the role of anthocyanozides in the prevention of retinal ganglion cell death. Russian ophthalmological journal. 2018; 11 (3): 101-6 (In Russian). doi: 10.21516/2072-0076-2018-11-3-101-106